Characterization of the extensive goat production system in the Altiplano of Tamaulipas, Mexico - Vázquez-Rocha, Lizeth; Vázquez-Armijo, José Fernando; Estrada-Drouaillet, Benigno; Martínez-González, Juan Carlos; López-Villalobos, Nicolás; López-Aguirre, Daniel (Ecosistemas y Recursos Agropecuarios, 2024)
In Tamaulipas extensive goat production systems in the semi-arid region of the Altiplano contribute annually with the production of 41% of live animals and 87% of milk in the state. The objective of the study was to characterize the goat production units in the municipalities of Jaumave, Bustamante and Tula, in which a significant number of production units are located. Through the application of structured surveys conducted in December 2021 and January 2022, socioeconomic, nutritional, productive, reproductive, and sanitary information was obtained from 40 goat production units. Data was analyzed using principal component factor analysis and a cluster analysis with the Statistical Program for Social Sciences (SPSS version 24). Four factors (management, production, grazing and reproduction) explained most of the total variation of the data and four groups of production units were determined. The characterization of the extensive goat production system in the Altiplano of Tamaulipas is described in general terms with management and production variables. However, the analysis of the typologies of production units showed heterogeneity in the system, in this sense, the differences between the means of the groupings that stood out the most were zootechnical purpose, reproduction, production and annual income. Underfeeding, scarce water sources and poor reproductive management are associated with low productivity and high animal mortality.